THE ROLE OF WESTERN LEGISLATIONS AND LAWS IN PROTECTING CHILDREN FROM ADVERTISEMENT - Zamoum, Khaled (ALBAHITH ALALAMI, 2020)
This study aims to identify the most important legislatures and legal frameworks pertaining to advertisement for children. It focuses on the western approach, which is characterized by the variety of its perspectives in presenting issues and in identifying problems. However, if studies show that there is a certain awareness about the advertisement impact on children, it is obvious that most of legislatures reject the laws restricting the broadcast advertising spots intended for children under 12 years of age, with the exception of the Swedish and the Canadian province of Quebec experiences, which opted for total ban on advertising spots broadcast messages targeting children.The study concluded that most of the studied Western experiments adopt preventive legislative policies, which aim mainly to educate advertisement agencies and businesses owners about psychological, social, and health effects, as well as other damages caused by some advertisement and commercial messages, especially those related to child's health.